Multiplex Polymerase Chain Reaction Based Typing of Staphylococcal Chromosomal Cassette mec of Methicillin Resistant Staphylococcus aureus from Selected Hospitals in Lahore - T, Romeeza; R, Naeem; A, Nadeem (IIUM Medical Journal Malaysia, 2010)
Introduction: Staphylococcus aureus is one of the leading causes of nosocomial infections. Prevalence of methicillin resistant Staphylococcus aureus (MRSA) has been reported in up to 42% of isolates in Pakistan. Methicillin resistance is encoded by the mecA gene and it is transferred by a unique genetic vector called staphylococcal chromosomal cassette (SCCmec). Depending upon the selection pressures of antibiotics, different types of SCCmec elements may prevail in different parts of the world. Materials and Methods: Therefore, this study was designed to fi nd out the major SCCmec types present in selected hospitals of Lahore. For this purpose thirty fi ve MRSA isolates were collected. These strains were reconfi rmed and SCCmec types were determined by multiplex PCR. Results: It was found that 21 (60%) isolates possess SCCmec type IA while 14 (40%) isolates possess SCCmec type IIC. Conclusion: These cassettes are shown to be multiresistant and have not been reported in other Asian countries so far.